Intellectual Property Protection of Indigenous Peoples in Indonesia: Quo Vadis? - Anis Mashdurohatun; Ariy Khaerudin; Teguh Prasetyo (Fakultas Hukum, Universitas Warmadewa, 2020)
Illicit used of intellectual property protection of indigenous peoples which are increasingly exploitative and leaving the existing values, and it’s happen over the world. Paradox government need it for raw material in creative economic but there’s no law to protect. The aim of this study is to describe dilemma of law patronage for Intellectual property of Indigenous People. Method for this study used library research. The values of justice in the use of traditional cultural expressions are carried out proportionally and balanced by harmonizing the values of individuals with communal values. Based on it ought to palladium with legal system that preserve behalf indigenous peoples in order to achieve legal objectives (Justice, certainty and expediency).